Virotherapy research in Germany: from engineering to translation - Ungerechts, Guy; Engeland, Christine Elisabeth; Leber, Mathias Felix; Springfeld, Christoph (Human gene therapy, 2017)
Virotherapy is a unique modality for the treatment of cancer with oncolytic viruses (OVs) that selectively infect and lyse tumor cells, spread within tumors, and activate anti-tumor immunity. Various viruses are being developed as OVs preclinically and clinically, several of them engineered to encode therapeutic proteins for tumor-targeted gene therapy. Scientists and clinicians in German academia have made significant contributions to OV research and development, which are highlighted in this review paper. Innovative strategies for “shielding,” entry or postentry targeting, and “arming” of OVs have been established, focusing on adenovirus, measles virus, parvovirus, and vaccinia virus platforms. Thereby, new-generation virotherapeutics have been derived. Moreover, immunotherapeutic properties of OVs and combination therapies with pharmacotherapy, radiotherapy, and especially immunotherapy have been investigated and optimized. German investigators are increasingly assessing their OV innovations in investigator-initiated and sponsored clinical trials. As a prototype, parvovirus has been tested as an OV from preclinical proof-of-concept up to first-in-human clinical studies. The approval of the first OV in the Western world, T-VEC (Imlygic), has further spurred the involvement of investigators in Germany in international multicenter studies. With the encouraging developments in funding, commercialization, and regulatory procedures, more German engineering will be translated into OV clinical trials in the near future.
Gesehen am 08.10.2018